Association Between Baseline Meniscal Symptoms and Outcomes of Operative and Nonoperative Treatment of Meniscal Tear in Patients With Osteoarthritis. Issue 8 (6th May 2022) - MacFarlane, Lindsey A.; Yang, Heidi; Collins, Jamie E.; Brophy, Robert H.; Cole, Brian J.; Spindler, Kurt P.; Guermazi, Ali; Jones, Morgan H.; Mandl, Lisa A.; Martin, Scott; Marx, Robert G.; Levy, Bruce A.; et al.
Abstract : Objective: Patients with meniscal tears reporting meniscal symptoms such as catching or locking have traditionally undergone arthroscopy. The present study was undertaken to investigate whether patients with meniscal tears who report meniscal symptoms have greater improvement with arthroscopic partial meniscectomy (APM) than physical therapy (PT). Methods: We used data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial, which randomized participants with knee osteoarthritis (OA) and meniscal tear to APM or PT. The frequency of each meniscal symptom (clicking, catching, popping, intermittent locking, giving way, swelling) was measured at baseline and 6 months. We used linear regression models to determine whether the difference in improvement in Knee Injury and Osteoarthritis Outcome Score (KOOS) pain score at 6 months between patients treated with APM versus PT was modified by the presence of each meniscal symptom. We also determined the percentage of participants with resolution of meniscal symptoms by treatment group. Results: We included 287 participants. The presence (versus absence) of any of the meniscal symptoms did not modify the improvement in KOOS pain score between APM versus PT by >0.5 SD (all P interaction >0.05). APM led to greater resolution of intermittent locking and clicking than PT (locking 70% versus 46%, clicking 41% versus 25%). No difference in resolution of the other meniscal symptoms was observed. Conclusion: Meniscal symptoms were not associated with improved pain relief. Although symptoms of clicking and intermittent locking had a greater reduction in the APM group, the presence of meniscal symptoms in isolation should not inform clinical decisions surrounding APM versus PT in patients with meniscal tear and knee OA.